Peran dan Dampak Penerapan Teknologi Informasi dan Komunikasi dalam Pendidikan Agama Islam: The Role and Impact of Information and Communication Technology (ICT) Implementation in Islamic Religious Education - Basyari, Zen Anwar Saeful; Marwiji, Muh. Hasan (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
This research aims to explore the role and impact of the application of information and communication technology (ICT) in Islamic religious education, particularly in improving the learning process and learner engagement. Along with the rapid development of ICT, the importance of ICT integration in Islamic religious education is increasing. The method used is library research with a qualitative approach, where data is obtained from various scientific literature and relevant academic references. The results show that the application of ICT provides significant benefits, such as increased learning interactivity and wider accessibility of materials. However, challenges are also faced, especially related to the ethical use of ICT and the compatibility of its application with the principles of Islamic law. The implications of this research emphasize the importance of developing an Islamic religious education curriculum that integrates ICT in a balanced manner, taking into account religious values. The integration of ICT in Islamic religious education needs to be accompanied by appropriate supervision in order to maximize its effectiveness.